A formant analysis of common vowels in Singapore English - Lim, Shiyun (Nanyang Technological University, 2020)
Accent modelling in ASR for Inner Circle English varieties such as American English and British English have been largely successful due to a large repository of annotated data and years of research. However, in less extensive English varieties such as Singapore English, there is still a gap in the literature regarding annotated data for accent modelling. Using data collected in the IMDA National Speech Corpus, this study aims to annotate and analyse speech data pertaining to vowels in the linguistic repertoire of Singapore English. It also aims to compare the vowel formant transition of Singapore English to that of Inner Circle varieties. Preliminary results have found that there is no resemblance in vowel formant transition between Singapore English speakers and Inner Circle English speakers.